The Effect of the Cooperative Learning Model Type of Example Non-Example on Student Learning Competencies About Global Warming Material Grade VII Students Of Pariaman Junior High School - Marisa Defri; Ristiono Ristiono; Rahmawati Darussyamsu; Ganda Hijrah Selaras (Universitas Negeri Padang, 2020)
The problem that still often arises during learning is that the use of learning models by teachers is less varied. The learning strategy used by the teacher is inappropriate. In fact, it is not uncommon to find a learning process that is only teacher-centered. Many students are less daring to ask questions and give opinions and look bored during the learning process. This happens because teachers rarely use learning models, only refer to books, still use the lecture method and use less varied media. This results in students having low interest and learning competencies. This research was conducted at 4th Pariaman Middle School. This study included quasi-experimental research because variables cannot be fully controlled. The population in this study were all VII grade students of 4 Pariaman Junior High School who were registered in the 2018/2019 Academic Year. Sampling uses purposive sampling technique, so class VII5 is chosen as the control class and VII4 as the experimental class. The data of this study include knowledge competencies, attitude competencies, and skills competencies. Based on the results of the competency knowledge data analysis of students, the value of tcount = 2.95> t table = 1.71, in the attitude competency the value of t count = 3.09> t table = 1.71, and in the competency skill the value t = 1.72> t table = 1.71. The conclusion of this study is the application of Cooperative Learning model type Non-Example Example about the material of global warming has a meaningful influence on the competency of knowledge, attitudes, and skills of class VII students of SMP 4 Pariaman.